Sekwencjonowanie największego chromosomu Paramecium tetraurelia - przykład opracowania metody - Nowak, Jacek K. (Komitet Biotechnologii PAN, 2010)
The largest, megabase, somatic chromosome of P. tetraurelia was isolated and sequenced in order to explore its organization and gene content. The AT-rich chromosome is compact with very small introns, short intergenic regions and a coding density of at least 74%, higher than that reported for budding yeast or any other free-living eukaryote. Homology to known proteins could be detected only for 57% of the 464 potential protein coding genes. Subsequently, the megabase chromosome sequence was used during the whole genome sequencing project as a reference to evaluate sequence assembly and gene annotation accuracy. In a pilot project of the global analysis of P. tetraurelia gene expression during autogamy, DNA microarrays were used. Statistical data analysis allowed the identification of four clusters of co-ex- pressed genes. Screening for silencing phenotypes of 15 autogamy specific genes revealed that 4 genes were essential during vegetative growth and 3 others were essential for successful sexual process.
prace przeglądowe
Keywords: biotechnologia